Voting Behavior Patterns of Gen Z in the 2024 Indonesian Presidential Election in DKI Jakarta - Kholilah Yahya, Nadiyah; Dewi Warsoyo, Atika; Muchamad Ghani, Irpan (Journal of Law, Politic and Humanities, 2024)
This study  aims to analyze the voting behavior patterns of Generation Z (Gen Z) in the 2024 Indonesian Presidential Election in DKI Jakarta, focusing on the influence of social, psychosocial, and rational choice variables on voting behavior. This study uses a quantitative survey method with questionnaires distributed to Gen Z respondents in DKI Jakarta. Data were analyzed using Structural Equation Modeling (SEM) to examine the relationships between social, psychosocial, and rational choice variables with voting behavior. This research is a continuation of previous studies discussing the voting behavior patterns of first-time voters analyzed using voting behavior theory with social, psychological, and rational choice approaches. However, to support the novelty of the analysis, this research focuses on the behavior patterns of Gen Z in the 2024 presidential election. The findings reveal that in the digital era, social media plays a crucial role in shaping Gen Z's political preferences, while psychosocial factors, such as candidates' historical backgrounds and emerging issues, have a significant direct influence on Gen Z's voting behavior. These findings provide essential insights for policymakers and political practitioners in designing effective communication strategies for Gen Z and enrich the academic literature on young voters' behavior in the digital era.